Comparison of efficacy of deep brain stimulation, repeat transcranial magnetic stimulation, and behavioral therapy in Tourette syndrome: A systematic review and Bayesian Network Meta-Analysis. Issue 10 (October 2022) - Lin, Xiaofeng; Lin, Fabin; Chen, Huiyun; Weng, Yanhong; Wen, Junping; Ye, Qinyong; Chen, Chunmei; Cai, Guoen
Abstract: Background: Tourette syndrome (TS) is an incurable neuropsychiatric disorder. Deep brain stimulation (DBS), repeat transcranial magnetic stimulation (rTMS), and behavioral therapy (BT) are all effective treatments. However, the comparison of therapeutic effect of these three therapies is lacking. Methods: A systematic literature search was conducted for randomized controlled studies (RCT). A network meta-analysis by R4.04 software according to Bayesian framework were performed. Results were meta-analyzed and network meta-analyzed to evaluate and compare the efficacy of DBS, rTMS and BT in TS patients. Results: A total of 18 randomized controlled studies with 661 participants were included. The Yale Global Tic Severity Scale (YGTSS) and the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) were utilized to evaluate the symptoms of TS. All three treatments improved the tic symptoms of TS [DBS 12.11 (95%CI 7.58–16.65); rTMS 4.96 (95%CI 1.01–10.93); andBT 11.72 (95%CI 10.42–13.01)]; and obsessive-compulsive symptom [DBS 4.9 (95%CI 1.13–8.67); rTMS 5.28 (95%CI 0.21–10.77); and BT 1.61 (95%CI 0.74–2.48)]. The cumulative probability results showed that DBS had the best effect on the improvement of tic symptoms, followed by BT; and rTMS was ranked last. However, in terms of improvement of obsessional symptoms, rTMS was ranked first, DBS was ranked second, and BT was ranked last. In addition, the meta regression analysis of YGTSS in DBS, rTMS and BT has significant difference (P = 0.05). Limitation: Due to the lack of quantitative indicators, we did not perform a network meta-analysis of the side effects of the three treatments. Conclusion: Our study showed that DBS, rTMS, and BT are effective in TS. DBS causes the best improvement in tic symptoms, and rTMS is the most effective in improving the obsessive-compulsive symptoms. Abstract : Tourette syndrome; Deep brain stimulation; Repeat transcranial magnetic stimulation; Behavioral therapy; Bayesian Network Meta-Analysis.